Treatment of ADHD in a patient with Brugada syndrome: a case report and a brief review - Pınar Demir Gündoğmuş; İbrahim Gündoğmuş; Abdulkadir Karagöz; Murat Kıyançiçek; Alişan Burak Yaşar; Ayhan Algül (Psychiatry and Clinical Psychopharmacology, 2018)
The Brugada syndrome is one of the common causes of sudden cardiac arrest in healthy-appearing adults. The use of drugs in the treatment of this disease may give variable and unwanted results. Attention-deficit/hyperactivity disorder (ADHD) is a chronic neurobehavioural disorder which has begun to be noticed in adults as much as children. In our case, we present a 39-year-old male patient with an ADHD who was diagnosed with the Brugada syndrome during a routine examination and we discuss the treatment of this case. The association of ADHD and Brugada syndrome has not been previously reported in any clinical study. As far as we know, the present case is the first article in the literature to discuss the follow-up and treatment of ADHD in a patient with the Brugada syndrome. We observed all medical and non-medical treatment methods for ADHD treatment and discussed these methods such as psychostimulants, atomoxetine, bupropion, and psychotherapy.